Arbor cultivation method of tamarix chinensis - ZHU WENCHENG; WANG XIA; WANG SHOUGUO; WANG LILI; LIU DEXI; LI YONGTAO; WEI HAIXIA; YANG QINGSHAN; DONG YUFENG; ZHOU JIAN (2018)
The invention discloses an arbor cultivation method of tamarix chinensis. A bacterial solution is added into a culture substrate for fermentation culture, so that growth of pathogenic bacteria in thesubstrate is inhibited, the structure and nutritional ingredients of the substrate are prevented from being damaged, and the method is safe and efficient; root hair of seedlings is removed one week after rooting of the seedlings, and then the seedlings are inserted into the culture substrate again so that the bending degree of branches can be reduced, and high yield and high quality can be kept; the branches below two thirds of the height of the seedlings are trimmed regularly so that growth of the trunks of the seedlings into arbors can be promoted, the arbor tamarix chinensis can be obtained, and the economic value and the ecological value of the tamarix chinensis are improved. 本发明公开了种柽柳的乔木化栽培方法，栽培基质加入菌液进行发酵培养，抑制基质中病原菌的生长，避免破坏基质的结构和营养成分，安全高效；在种条生根周后，将种条的根须去除，然后重新插入栽培基质，能够减小枝条的弯曲度，保持高产高质；定期将苗木高度三分之二以下的枝条修剪掉，能够促进苗